A dendroclimatological analysis of fir (Abies alba Mill.) growth in the Borja mountain area of Bosnia and Herzegovina - Jović Goran; Dukić Vojislav; Stajić Branko; Kazimirović Marko; Petrović Danijela (Glasnik Šumarskog Fakulteta: Univerzitet u Beogradu, 2018)
This paper presents the results of a dendroclimatological analysis of the growth of fir trees in the Borja mountain area, Bosnia and Herzegovina. The required data were taken in 2 sites, and the sample covered a total of 60 series of radial increment (15 dominant trees per site with two cores). Standard dendrochronological processing and data analyses using the Coffecha and Arstan software were performed. The preliminary 137-years long regional fir chronology for the Borja mountain area was obtained. The obtained results of the correlation analysis between the radial increment index of the defined chronology, on the one hand, and the monthly precipitation and temperature, on the other, showed that higher summer precipitation significantly increased the increment of fir, and that the increase in temperature in these months did not not cause a significant increment reduction. However, the results of the FAI drought index application for the stated purposes have shown that more intense droughts in the summer months can cause a significant reduction in the increment of fir in a given area.